2020
DOI: 10.1002/ece3.7019
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling effects of disturbance severity and frequency: Does bioindication really work?

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Deeper insights into the disturbance regimes shaping riparian ecosystems revealed that different components of ecological disturbances can show opposing trends. At the coarse spatial scale, the disturbance severity increases downstream whereas the disturbance frequency decreases along rivers (Lepori & Hjerdt, 2006; Pielech & Czortek, 2021). Recent analyses revealed that many traits show different responses to the severity and frequency of ecological disturbances (Herben et al., 2018; Midolo et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deeper insights into the disturbance regimes shaping riparian ecosystems revealed that different components of ecological disturbances can show opposing trends. At the coarse spatial scale, the disturbance severity increases downstream whereas the disturbance frequency decreases along rivers (Lepori & Hjerdt, 2006; Pielech & Czortek, 2021). Recent analyses revealed that many traits show different responses to the severity and frequency of ecological disturbances (Herben et al., 2018; Midolo et al., 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the longitudinal (upstream–downstream) gradient is frequently discussed in biodiversity studies. Some vital physical properties change continuously along this gradient, including water velocity, width of the channel, light availability, accumulation to erosion ratio, and disturbance regimes, among others (Lite et al., 2005; Naiman et al., 2005; Pielech & Czortek, 2021). These factors shape the riverine biodiversity and are responsible for species turnover along the longitudinal gradient.…”
Section: Introductionmentioning
confidence: 99%